Modified household pressure cookers as Hydrothermal Reactor for Production of Carbon Dots from Fish Scale Waste - Dolfie Paulus Pandara; Stepanus Tangdan; Guntur Pasau; Ferdy Ferdy; Maria Daurina Bobanto; Gerald Hendrik Tamuntuan; Ping Astony Angmalisang; Kawengian Warouw Alex Masengi; Maureen Kumaunang (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2025)
Recent advancements in the synthesis of carbon dots utilizing basic equipment are crucial for their large-scale production. This study explores the use of household pressure cookers to synthesize carbon dots from fish waste. A thermocouple and manometer are integrated into the cooker to regulate temperature and monitor pressure. Optimization of the equipment reveals that heating 2000 mL of distilled water to 100°C requires 20, 30, and 32 minutes with power inputs of 800 W, 700 W, and 600 W, respectively. The modified cooker achieves optimal pressure and temperature at 2.4 bars, 1.7 bars, and 1.5 bars, and 136°C, 123°C, and 122°C after 60 minutes of heating with the same power inputs. These results demonstrate that a household pressure cooker can effectively synthesize carbon dots. Experiments using dried Red Snapper fish spray powder, both unground and ground, at 800 W, 700 W, and 600 W, reach optimal pressure of 2.4 bar in 36, 49, and 58 minutes, and temperatures of 128°C, 131°C, and 136°C. Carbon dots are synthesized from fish scales as fine fibers with a 1:5 weight ratio of scales to distilled water, employing 600 W power, 2.4 bar pressure, 136°C temperature, 58 minutes of boiling, 5 minutes of centrifugation at 3500 rpm, and 45 minutes of ultrasound at 42 kHz. The formation of carbon dots is confirmed by an absorption peak at 405 nm in the UV-Vis spectrum, indicating high absorbance and bright blue fluorescence. Further investigation is required to optimize equipment using various fish scales and purification processes